Tanggapan Peserta terhadap Pelaksanaan Kegiatan Pelatihan Usaha Kecil Menengah Kota Padang di BPPD Provinsi Sumatera Barat - Sakinah Hasti; Wisroni Wisroni; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is motivated by the high participation and activeness of the trainees allegedly because of the positive response from the participants of small medium business training to the implementation of the training itself. This study aims to describe the training participants' responses to training materials, training methods, training media, and training instructors. This research is quantitative descriptive research. The population in the study as many as 100 people. Sample 40 people with stratified random sampling technique. Data collection techniques used questionnaires with data collection tools in the form of a list of statements. Data analysis techniques use percentage calculations. The results showed that the participants' responses were positive, as seen from the high percentage of results for the answers agreed and strongly agreed. The result of the research is that the training participants' responses to training materials, training methods, training media, and training instructors are positive. Research suggestions to training instructors, in order to maintain the performance of their training, training providers, in order to facilitate instructors in carrying out their future tasks, and as inputs for other researchers to examine other variables concerning training of small and medium enterprises.